2018
DOI: 10.1016/j.rmed.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of treatments in primary spontaneous pneumothorax: A systematic review and network meta-analysis of randomized clinical trials

Abstract: Aspiration and tube drainage have no significant difference in treating patients with first episode of PSP regarding recurrence. Aspiration reduced hospitalization days when compared with tube drainage. Thoracotomy with mechanical pleurodesis and VATS with or without pleurodesis are not significantly different in preventing recurrence in patients with recurrent or persistent PSP. VATS alone reduced complications compared with others treatments except for thoracotomy with abrasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 50 publications
1
49
0
7
Order By: Relevance
“…A meta-analysis comparing the different combinations of intraoperative treatment for primary spontaneous pneumothorax found that wedge resection combined with chemical pleurodesis, as well as wedge resection, combined with both mechanical pleural abrasion and chemical pleurodesis, had the lowest recurrence rates. Although Video-Assisted Thoracoscopy in the Management of Primary and Secondary Pneumothorax DOI: http://dx.doi.org /10.5772/intechopen.83669 the complications of these procedures were not taken into account favoring chemical or mechanical pleurodesis, in addition to wedge resection to remove the source of the air leak [21,22]. Mechanical pleurodesis should be considered on a case-by-case basis with good clinical judgment.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis comparing the different combinations of intraoperative treatment for primary spontaneous pneumothorax found that wedge resection combined with chemical pleurodesis, as well as wedge resection, combined with both mechanical pleural abrasion and chemical pleurodesis, had the lowest recurrence rates. Although Video-Assisted Thoracoscopy in the Management of Primary and Secondary Pneumothorax DOI: http://dx.doi.org /10.5772/intechopen.83669 the complications of these procedures were not taken into account favoring chemical or mechanical pleurodesis, in addition to wedge resection to remove the source of the air leak [21,22]. Mechanical pleurodesis should be considered on a case-by-case basis with good clinical judgment.…”
Section: Managementmentioning
confidence: 99%
“…When comparing VATS to other treatment modalities, such as aspiration, chest tube drainage, and pleurodesis, a recent meta-analysis of all available randomized control trials showed that VATS had the most favorable results with regard to recurrence and hospitalization days [21,22]. The addition of pleurodesis to VATS bullectomy compared to VATS bullectomy alone further decreases recurrence rates, although this strategy comes with associated complications that include pain [21,22]. Given the increased complications that arise from pleurodesis, some novel attempts at replacing the procedure, and at the same time achieving the same goal of promoting adhesions, have been developed.…”
Section: Managementmentioning
confidence: 99%
“…The recurrence rate is reported to be between 17 and 54% [5][6], with the majority of recurrences in the first year after the primary event [7]. Recurrence rate can be reduced by surgical pleurectomy or thoracoscopic pleurodesis [8]. Initial management of PSP has been subject of ongoing debate [4,8], with a trend towards a more conservative approach using manual aspiration and outpatient treatment [4,6,[8][9][10][11][12].…”
mentioning
confidence: 99%
“…Recurrence rate can be reduced by surgical pleurectomy or thoracoscopic pleurodesis [8]. Initial management of PSP has been subject of ongoing debate [4,8], with a trend towards a more conservative approach using manual aspiration and outpatient treatment [4,6,[8][9][10][11][12]. Manual aspiration has been shown to be effective in approximately two-thirds of patients [8] and is as equally effective as chest tube drainage [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation